Penerapan Pop-Up Book Materi Bagian Tumbuhan untuk Anak Tuna Grahita di SLB-C Rindang Kasih Magelang - Erna Merlianda; Arlita Wigati; Agil Tohirul Huda; Laras Anggrahita; Fiki Ifada; Rifky Rahmandita Tarigan; Ferisa Prasetyaning Utami; Weni Anggraeni (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2025)
Children with intellectual disabilities experience limitations in intellectual functioning that may affect their cognitive, affective, and motor abilities. Therefore, they require appropriate learning approaches, particularly for abstract topics such as plant parts in biology. This study aimed to develop and implement a pop-up book as a learning medium to improve the understanding and engagement of students with intellectual disabilities at SLB-C Rindang Kasih Magelang, a special education school. A participatory approach was employed through several stages: problem identification through classroom observation and teacher interviews; development of a pop-up book on plant parts with three-dimensional elements; implementation of the medium in a two-hour learning session involving three students; and evaluation using a teacher satisfaction questionnaire based on a Likert scale. The medium was designed with colorful visuals, simple language, and interactive quizzes to support comprehension. The evaluation results indicated that the pop-up book was perceived as highly effective (78%), practical (69.3%), and highly engaging (80%). In addition, during the implementation, the students showed enthusiasm, active interaction, and improved understanding of the material. The medium also facilitated interactive learning that was appropriate to the cognitive needs of students with intellectual disabilities. This study contributes to the development of innovative learning media for children with intellectual disabilities and recommends broader development and implementation in special education settings.